EFEKTIFITAS MANAJEMEN SUMBER DAYA MANUSIA PADA PENDIDIK DAN TENAGA KEPENDIDIKAN DI MTs NEGERI 2 PESAWARAN - RAHMATIYAH; MUSTAFIDA (UNISAN JURNAL, 2024)
This study uses a type of qualitative research with a case study design. Data and documents were collected and compiled using in-depth interview techniques, participant observation and documentation studies. the results of this job analysis are carried out filling and placing personnel in positions according to intellectual capacity, capability, work experience and exemplary. (1) the withdrawal and selection of GTT and PTT candidates is carried out based on considerations of academic, non-academic achievements and good morals. (2) the training and development of human resources that are carried out still tend to measure the success and failure of training in terms of implementation, not oriented to whether effectively the training carried out is able to change the behavior and performance of the participants towards the goals of the madrasa. Keywords: Analysis of Human Resource Management in Educators and Education Personnel